FAKTOR-FAKTOR YANG MEMPENGARUHI DERMATITIS KONTAK YANG DILAMIOLEH PEKERJA: Literature Riview - Susilawati Susilawati; Ade Suri Lestari (CV. ADIBA AISHA AMIRA, 2022)
Occupational contact dermatitis is dermatitis that arises as a result of contact with chemicals at work, it must be differentiated from non-occupational contact dermatitis, namely contact dermatitis that arises due to contact with materials not related to work such as cosmetics, jewelry, or drugs. The method of this research is this research was conducted using the Literature Review method. The journal used is in accordance with the discussion of